Examining IRA Bots in the NFL Anthem Protest: Political Agendas and Practices of Digital Gatekeeping. (February 2021) - Yan, Grace; Pegoraro, Ann; Watanabe, Nicholas M.
With the understanding that the mass-participated mechanism of social media has led to an evolved lens of gatekeeping, this study incorporates the framework of digital gatekeeping to examine activities of Internet Research Agency (IRA) bots in the Twitter sphere of the National Football League anthem protest. To do so, the investigation employed data of IRA bots released from Clemson University. We conducted analysis by approaching bots' gatekeeping activities from three perspectives: the overall behavioral patterns, the discourses and underpinning ideologies, and communicative tactics to sustain attention on Twitter. The results revealed that the majority of tweets came from the right trolls and left trolls. Meanwhile, the activity level of the bots displayed high sensitivity to emergent political events. Importantly, the two types of bots orchestrated a gatekeeping agenda that propelled antagonistic, hyperpartisan politics. The right-wing trolls' tweets, in particular, propagated pro-White, malicious propaganda infiltrated with fake news. The results yield meaningful implications for digital gatekeeping, social media's complex roles in knowledge production related to athlete protest, and sport's engagement in broader political struggles in today's mediated culture.